A Forgotten Cause of Chronic Dizziness in the Elderly: Exercise‐Induced Vertebrobasilar Insufficiency due to Grade III Subclavian Steal Syndrome - Said Abdirahman Ahmed; Osman Farah Dahir; Abdijalil Abdullahi Ali; Abdishakur Abdiqadir Mahdi; Abdillahi Mohamed Abdi; Ahmed Elmi Abdi; Ahmed Shafie Aden; Ishak Ahmed Abdi; Mohamud Mire Waberi; Mohamed Abdullahi Mohamud; Abdullahi Mohamed Hassan Fujeyra; Mohamed Sheikh Hassan; et al. (Clinical Case Reports, 2026)
ABSTRACT Chronic dizziness in elderly patients, particularly when reproducibly triggered by upper limb exertion, should prompt evaluation for arm‐exertion‐provoked vertebrobasilar hypoperfusion due to subclavian steal syndrome. Duplex ultrasonography can identify complete retrograde vertebral artery flow and confirm complete Grade III subclavian steal physiology, highlighting a treatable vascular cause that may otherwise be misattributed to vestibular, medication‐related, or neurodegenerative disease.